Influence of phylogenetic, environmental, and behavioral factors on the gut bacterial community structure of dung beetles (Scarabaeidae: Scarabaeinae) in a Neotropical Biosphere Reserve - Jácome-Hernández, Alberto; Lamelas, Araceli; Desgarennes, Damaris; Huerta, Carmen; Cruz-Rosales, Magdalena; Favila, Mario E. (Frontiers in Microbiology, 2023)
Gut bacteria help dung beetles metabolize nutrients contained and synthesize those unavailable in their food, depending on the ecological scenario in which they develop. However, little is known about the influence of environmental and behavioral factors on the taxonomic composition of bacterial gut communities in Scarabaeinae beetles. To address this research topic, we analyzed thirteen tropical dung beetle species in the Los Tuxtlas Biosphere Reserve, Mexico, to understand how the beetle tribe, habitat, food preference, food relocation, and parental care influence the composition of gut bacterial communities. We found that beetle tribe is the primary factor impacting the taxonomic composition of gut bacterial communities. Among them, Deltochilini displayed the highest variability in diversity due to the different combinations of habitat and food preferences among its species. On the other hand, the other tribes studied did not exhibit such variable combinations. The habitat emerged as the second most influential factor, with forest-dwelling beetles displaying higher diversity. This can be attributed to the heterogeneous environments within tropical forests, offering greater diversity of food resources. In contrast, grassland beetles, living in more homogeneous environments and relying on cow feces as their main food source, exhibited lower diversity. Our findings suggest a correlation between bacterial diversity and food resource availability in complex habitats, such as tropical forests, which offer a wider array of food sources compared to simpler environments like grasslands.